O urbanismo e a paisagem desejada - Iracema Generoso de Abreu Bhering (2019)
This work aims to reflect on the landscape and translate these reflections into legal parameters and guidelines. The discussion about landscape transcends the discussion of theoretical-methodological sources and is associated to issues such as quality of life, utopian urban models and the revaluation of the landscape as a field of study, linked to environmental issues and popular participation. In order to do so, relevant elements of the landscape were investigated, such as slopes, amount of sunlight, topographical landscape, geomorphy, hydrography - almost a physiographic landscape, besides analyzing two plans in order to discover how far the landscape shaping elements are thought when legislating on a area. These analyzes are based on palpable elements that shape the space, since the landscape we are talking about seeks to have, above all, a degree of concreteness that makes it possible to subsidize the planning of an area.